Hydrostatic pressure and temperature effects on spectrum of an off-center single dopant in a conical quantum dot with spherical edge - Chnafi, M.; Belamkadem, L.; Mommadi, O.; Boussetta, R.; El Hadi, M.; El Moussaouy, A.; Falyouni, F.; Vinasco, J.A.; Laroze, D.; Mora-Rey, F.; Duque, C.A. (Superlattices and microstructures, 2021)
In this paper we have studied the spectrum of an off-center donor impurity confined in the GaAs conical quantum dot with spherical edge surrounded by finite and infinite confinement potential. By considering the effective mass approximation and using the finite difference and elements method, we have obtained the eigenenergies and the eigenfunctions of the nanosystem. The hydrostatic pressure and temperature effects as well as the displacement of the donor on the binding energy are investigated. Within the confinement effect, the variation of the dot angle and the radius of the conical quantum dot on the electron-donor properties are evaluated. The numerical findings show that the binding energy is very sensitive to the position of the impurity and the size of the conical quantum dot (radius and dot angle). The position of the donor impurity leads to control the way of the variation of the binding energy versus the conical angle. The study includes the effects of hydrostatic pressure and temperature. It is noted that the binding energy increases with hydrostatic pressure and decreases with temperature. Additionally, the results show that the diamagnetic susceptibility increases with the conical angle and decreases with the dot radius. Therefore, it has an effective influence on the small radius of the quantum cone. In addition, we have examined extensively the possible effect due to change of the geometric angle and different position of impurity on the permanent dipole moment created by the electron and the ionized atom. Our results indicate that the spectrum of the impurity is strongly related to the impurity positions and the dot angle of the nanodot. These different influences allow a good understanding of the spectrum of these nanoparticles, and facilitate the fabrication of new optoelectronic devices. •A donor atom confined in conical quantum dots with spherical edge.•The pressure dependent Γ-X crossover at the conduction band modifies the barrier potential.•The eigenvalues differential equations have been solved by using a two-dimensional finite difference method.•For the donor atom located at the quantum cone cap center, the binding energy decreases with the geometric parameters.•The average electron-impurity distance depends strongly from the pressure, temperature, and impurity position.